2008
DOI: 10.1111/j.1464-410x.2008.07891.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract phenotype of experimental autoimmune cystitis in mouse: a potential animal model for interstitial cystitis

Abstract: OBJECTIVE To examine bladder function in a newly developed experimental autoimmune cystitis (EAC) model in female SWXJ strain mice, as a potential animal model for interstitial cystitis (IC). MATERIALS AND METHODS In all, 20 SWXJ female mice were divided into two groups: an EAC group immunized with mouse bladder homogenate in complete Freund’s adjuvant (CFA) and a control group immunized with CFA alone. At 4 months after injection, the bladder function of some mice (six) was studied with 24‐h micturition habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 24 publications
0
47
0
Order By: Relevance
“…Experimental autoimmune cystitis (EAC) can be induced through immunization with bladder tissue components in rodents. These EAC models have been used to reproduce many clinical correlates of IC/BPS, offering a unique property for investigation of specific aspects of the disease such as cystitis pain and voiding dysfunction [10,23,24]. Using genetic engineering technology, we previously developed a transgenic EAC model (URO-OVA) that expresses the membrane form of the model antigen ovalbumin (OVA) as a self-antigen on the urothelium and develops bladder inflammation at 7–14 days after adoptive transfer of OVA-specific T cells for cystitis induction [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental autoimmune cystitis (EAC) can be induced through immunization with bladder tissue components in rodents. These EAC models have been used to reproduce many clinical correlates of IC/BPS, offering a unique property for investigation of specific aspects of the disease such as cystitis pain and voiding dysfunction [10,23,24]. Using genetic engineering technology, we previously developed a transgenic EAC model (URO-OVA) that expresses the membrane form of the model antigen ovalbumin (OVA) as a self-antigen on the urothelium and develops bladder inflammation at 7–14 days after adoptive transfer of OVA-specific T cells for cystitis induction [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the cystometric voided volume (VV) of the normal mouse varies widely between 29 and 168 l according to previous reports (9,17,23,24). However, these cystometric VVs are remarkably small compared with mouse spontaneous VVs estimated from voided spots on paper (ranging from 200 to 520 l) (12,16,22). It has been suggested that the low VV as measured by mouse cystometry can be attributed to the inhibition of bladder function caused by anesthesia (25), laparotomy, and bladder catheter placement.…”
mentioning
confidence: 99%
“…In SWXJ mice, the same immune challenge generates a similar immune IC with increased urination frequency, decreased volume per void, as well as lymphocytic infiltration and thickening of the lamina propria (32). A similar model with increased urinary frequency, mast cell accumulation and vascular congestion, has also been reported in Lewis rats by immunization with bladder homogenate (33).…”
Section: Activated Mast Cells and The Immune Response In Bladder Icmentioning
confidence: 57%